Safety and effectiveness of microdebrider bronchoscopy for the management of central airway obstruction. Issue 6 (25th July 2013) - Casal, Roberto F.; Iribarren, Juan; Eapen, George; Ost, David; Morice, Rodolfo; Lan, Charlie; Cornwell, Lorraine; Almeida, Francisco A.; Grosu, Horiana; Jimenez, Carlos A.
Abstract Background and objective Microdebrider bronchoscopy is a relatively new modality for the management of central airway obstruction (CAO) of both benign and malignant origin. Our objective was to describe our experience with this technique, with special attention to its safety and effectiveness. Methods We retrospectively reviewed cases of therapeutic bronchoscopies using microdebrider for CAO from two institutions (M.D. Anderson Cancer Center and Michael E. Debakey VA Medical Center, Houston) from August 2008 through February 2012. Results We identified 51 cases. Malignant CAO was detected in 36 cases (71%): non‐small‐cell lung cancer (n = 22), melanoma (n = 3), small‐cell‐lung cancer (n = 2), thyroid cancer (n = 2), esophageal carcinoma (n = 2), breast cancer (n = 2), and others (n = 3). Benign diseases included: papillomas (n = 8), granulation tissue (n = 3), and others (n = 4). Obstruction was purely endoluminal in 32 cases (63%). Pre‐treatment obstruction was severe in 25 cases (49%), moderate in 20 cases (39%) and mild in 6 (12%). Lesions were located in the trachea (n = 23), main stem bronchi (n = 25), and bronchus intermedius (n = 8), with some patients having more than one lesion. After tumor debulking with microdebrider, the residual airway obstruction was insignificant (n = 27 cases; 53%), mild (n = 23 cases; 45%), and moderate (n = 1; 2%). No major complications were encountered, only 2 patients had mild adverse events: one case of pneumomediastinum, and one self‐expandable stent damage requiring its removal. Two patients (4%) died within 30 days of causes unrelated to the procedure or the CAO. Conclusions Microdebrider bronchoscopy is a potentially safe and effective way to manage central airway obstruction of both malignant and benign origin.